PENGARUH FASHION HIJAB TERHADAP PERILAKU KONSUMTIF MAHASISWI FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PALANGKA RAYA - Sa'adatunnisa, Sa'adatunnisa (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2016)
Development of the world fashion at this time theis always increased. It can be demonstrated with the development of fashion hijab at this time. Many models are evolving hijab cause excessive purchasing behavior. Such behavior is the consumer behavior, is behavior that purchase goods or services in excess. For this study will focus on the effect on consumer behavior fashion hijab of student IAIN Palangkaraya to determine the effect on consumer behavior fashion hijab of student IAIN Palangkaraya with technique Product Moment Correlation analysis using SPSS 18.0 version.